PEMANFAATAN TEMPAT PENDARATAN IKAN (TPI) DI KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Wulandari, Tria; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Building Fish Landing Places (TPI) that ther stimuli are buildings constructed for thefishermen land their catch of fish. These buildings have been built but not yet enabled bythe local government, especially the Department of Marine and Fisheries Meranti IslandsRegency. This is because the Department has the authority to regulate and supervise theactivities of marine and fisheries. Peneliitian purpose of this is to know the problemsfaced by the Department of Marine and Fisheries in the functioning of Fish LandingPlaces (TPI).Arrangement is to create a way to make a pekerjan have goals, direction to be achieved,sby knowing the existing procedures. This study used a qualitative descriptive method.Data were obtained from the interview data, documentary studies, and field observations.Informants in this study are those relating to the discussion of the function of FishLanding Places (TPI) is.The results showed that in the discussion of the function of pemanfaataan Fish LandingPlaces (TPI) is not able to function because of the absence of directives from the centralgovernment to the regions, and because of inadequate facilities. Furthermore, theconstraints for the fishermen are long distance and weather influences.Keywords. Place Pendaratn Fish, Function Department, Local Government